The Politics of the Public Plate: School Food and Sustainability - Morgan, Kevin (The International Journal of Sociology of Agriculture and Food, 2014)
The main themes I want to address in this speech are the following: first, I start with where we began 14 years ago looking at the public plate with respect to school food, and I end up looking at cities because this is the transition that I personally did. I started with school food provisioning and ended up with urban food planning (Morgan, 2009). During this period the school food agenda has moved on and expanded, and it is now connecting with an exciting array of topics to do with urban food politics, policy and sustainability in the food system. This is what I feel is unique about food: its multifunctional capacity to link up with an array of other important issues. Clearly hunger and malnutrition are key topics in food studies around the world, but we can never reduce food studies to nutrition or, for that matter, economics. Second, I will address some of the barriers to creative public food procurement. Third, the compelling work of some school food pioneers over the last 14 years will be examined and, finally, I will show some examples of what civil-society groups are doing in several cities with pioneering municipalities, trying to promote sustainability through their food procurement policy.